HYBRID CONTRACT ACCORDING TO SHARIA ECONOMIC LAW - Jamaludin, Ijang (Journal of Economicate Studies, 2017)
Sharia law is charged with guiding how to conduct economic activities in order to be safe and happy to the afterlife. Sharia economic activities especially in sharia financial institutions are increasingly varied following the global economic development, the innovation of Sharia Financial Institution products become a necessity. Single agreement as the core of a transaction is not able to accommodate the increasingly complex needs of transactions, the presence of hybrid contact as a transformation of the contract leads to the development of LKS on the one hand and generate a spicy criticism related to its validity on the other side. This paper through literature approach trying to analyze hybrid contact in terms of ijtihad methodology related to the theory used madhab Hanafi in view the legal consequences. The result that the Hybrid contract is al-mukharij min al-mazaiq / hilah as a way out as well as the benefit to avoid the practice of usury, and resulted in legal consequences as a contract.